Pengaruh Upacara Bendera dalam Meningkatkan Semangat Nasionalisme pada Peserta Didik di SMAS St. Petrus Kewapante - Kristina Diana; Nur Chotimah (Politeknik Kampar, 2023)
This research aims to find out one of the efforts to instill the spirit of nationalism in students through the flag ceremony at SMAS ST.Petrus Kewapante school. This research uses a descriptive qualitative method. The informants in this study were School Principal, Civic Education Teacher, Student Affairs Teacher, and Students of SMAS ST.Petrus Kewapante. The data collection techniques used were observation, interview, documentation. Data analysis techniques in the form of data collection, data reduction, and data verification.The results of this study indicate that: In essence, teachers and students understand the spirit of nationalism as a homeland attitude that is important for every citizen including students. The flag ceremony at school is also considered important as an effort to strengthen the spirit of nationalism of students.